Playing as a tool to help children in child development - Flavia Lopes, Ana; Julia Guimarães, Ana; Tak Parizotto, Gabriela; Amarães, Luciana; Vieira, Silmara; Claudia Monzon Zampoli, Ana (Seven Editora, 2023)
The present study aimed to present the importance of playing as a tool to help child development, seeking to bring a more interactive knowledge about the theme addressed. During the project, we addressed fundamental issues such as the importance of playing, potential development, organization of the environment and activities that favor the psychosocial development of the child in the act of playing.  DOI: https://doi.org/10.56238/tfisdwv1-031